(untitled) (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
Pure economic theory is a powerful tool for analyzing rational activity and its effective coordination. If reasonable and effective movement towards a goal is a characteristic feature of a person, and ethics and politics try to promote it at the individual and social levels, then it is clear that both are forced to resort to the economic principle and economic theory.